Virus-associated chronic endometritis: treatment options - Natalia I. Tapilskaya; Gulrukhsor Kh. Tolibova; Tatiana G. Tral; Alevtina M. Savicheva; Ruslan I. Glushakov; Gavkar A. Sadikova; Olga V. Budilovskaya; Anna A. Krysanova; Alexander M. Gzgzyan; Olesya N. Bespalova (IP Berlin A.V., 2022)
Aim. To evaluate the effectiveness of Alloferon (Allokin-alfa) in the complex treatment of virus-associated chronic endometritis (CE) in patients with infertility, papillomavirus infection (PVI) persisting in the uterine cavity, and recurrent herpes-virus infection localized in the genital area. Materials and methods. A prospective (n=33) open randomized (2:1) study was conducted to assess the efficacy of Alloferon (Allokin-alfa) in the complex treatment of CE in patients with infertility, PVI, and recurrent herpes-virus infection, aged 25 to 37 years (median age 31 [29; 32.5] years). All patients received valacyclovir therapy at 500 mg once daily for 30 days from the day of randomization. Patients in the main group (n=21) simultaneously with the start of antiviral therapy received Allokin-alfa as 9 subcutaneous injections once every two days (one injection every other day). The uterine cavity microbiota of the patients was assessed 3 months after treatment, and histological and immunohistochemical studies of endometrial biopsy specimens were performed. Results. The microbiological data analysis showed HPV elimination in 71.4% vs 16.7% of patients in the alloferon and control groups, respectively (2 7.102, p=0.008). Also, in the main group, a significant decrease in the severity of CE (2 27.586, p0.001) and p16ink4a protein expression levels (2 6.17, p=0.013) were observed. Conclusion. In the treatment of virus-associated CE, the addition of alloferon to virus-suppressive therapy leads to higher rates of HPV elimination from the uterine cavity and significantly reduces the severity of CE.